AN ANALYSIS OF EDUCATIONAL VALUES IN â€œTOTTO-CHAN: THE LITTLE GIRL AT THE WINDOWâ€ BY TETSUKO KUROYANAGI BASED ON PAULO FREIREâ€™S PERSPECTIVE - Jamaluddin, Jamaluddin; Ghofur, Abd. (Institut Agama Islam Negeri Madura, 2020)
The novel